Transformasi Ekonomi Daerah Kepulauan Riau yang Inklusif dan Berkelanjutan Melalui Triple Konsep: Pariwisata, Ekonomi Biru, dan Kerjasama Internasional Indonesia Malaysia Thailand-Growth Triangle (IMT-GT) - Weldy Riawan; Akbar (Jurnal Archipelago, 2025)
The regional advantage of   Riau Islands Province are it has the best tourism destinations, vast seas and abundant potentials, as well as  strategic geographical location with neighboring countries, but in reality these advantages has not been able to increase regional economic growth. There is a problem of decreasing economic growth accompanied by increases and decreases in the percentage of poverty levels that occur every year. The growth rate in the GRDP level also looks less satisfactory. Based on the regional advantages with declining economic growth conditions, this indicates that there is a gap so   inclusive and sustainable economic transformation is necessary. The research objective is to determine the development of economic transformation by examining triple concepts (tourism, blue economy, and international cooperation). This research is interesting to be further investigated because currently there are no studies that discuss international cooperation in achieving inclusive and sustainable economic transformation. This research method is descriptive qualitative to better understand economic transformation through analysis which is described into triple concepts. The results shows that the tourism concept and the blue economy concept as part of the inclusive and sustainable economic transformation needed for the development of flagship tourist attractions. Support from  the IMT-GT international cooperation concept would be able to increase the economic growth of the Riau Islands Province.